Special Therapy and Psychosocial Needs Identified in a Multidisciplinary Cancer Predisposition Syndrome Clinic. Issue 2 (March 2019) - Groves, Andrew P.; Gettinger, Katie; Druley, Todd E.; Kozel, Beth A.; Shinawi, Marwan; Mohrmann, Caroline; Henry, Jennifer; Jacobi, Celina; Trinkaus, Kathryn; Hayashi, Robert J.
Abstract : Identification of patients with cancer predisposition syndromes (CPSs) can provide vital information to guide care of an existing cancer, survey for future malignancy, and counsel families. The same underlying mutation responsible for a CPS may also result in other phenotypic abnormalities amenable to therapeutic intervention. The purpose of this study was to examine patients followed in our multidisciplinary CPS clinic to determine the prevalence and scope of medical and psychosocial needs. Data from a baseline evaluation of a single-center patient registry was reviewed. Eligible patients included those with a known or suspected CPS. Over 3 years, 73 patients consented and had successful follow-up. Utilization rate of special therapies, defined as speech therapy, occupational therapy, and/or physical therapy, in the CPS population was 50.7%, significantly higher than a representative sample of children with special needs. Prevalence of 504/IEP (Individualized Education Program) utilization was 20.5%. Patients with CPSs have a high prevalence of medical and psychosocial needs beyond their risk for cancer, for which early screening for necessary interventions should be offered to maximize the patient's developmental potential. Future research is needed to further define the developmental and cognitive phenotypes of these syndromes, and to evaluate the effectiveness of subsequent interventions.